2019
DOI: 10.4269/ajtmh.19-0249
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Seasonal Variation in Insecticide-Treated Net Use among Those with Access

Abstract: . Seasonal variation in the proportion of the population using an insecticide-treated net (ITN) is well documented and is widely believed to be dependent on mosquito abundance and heat, driven by rainfall and temperature. However, seasonal variation in ITN use has not been quantified controlling for ITN access. Demographic and Health Survey and Malaria Indicator Survey datasets, their georeferenced data, and public rainfall and climate layers were pooled for 21 countries. Nine rainfall typologies we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 66 publications
7
33
0
Order By: Relevance
“…Outdoor sleeping and large-scale socio-cultural events may also increase during this time and sleeping patterns may differ during planting and harvesting seasons [49,70]. ITN use can also vary seasonally due to factors such as heat, mosquito density, and perceived malaria risk [71]. Disaggregation of these indicators by age and sex can help programmes to further target interventions by demographic group, where needed.…”
Section: Discussionmentioning
confidence: 99%
“…Outdoor sleeping and large-scale socio-cultural events may also increase during this time and sleeping patterns may differ during planting and harvesting seasons [49,70]. ITN use can also vary seasonally due to factors such as heat, mosquito density, and perceived malaria risk [71]. Disaggregation of these indicators by age and sex can help programmes to further target interventions by demographic group, where needed.…”
Section: Discussionmentioning
confidence: 99%
“…Only LLINs that are being used can contribute to malaria transmission control, and LLINs that are present in households but are stored away and remain in good condition are useless until used. LLIN use, in addition to depending on presence, physical and chemical status of LLINs, depends on a plethora of factors including product quality, geographically specific use practices, knowledge about their benefits, and seasonally varying factors such as mosquito nuisance levels, temperature and humidity which impact the comfort level inside a LLIN [ 25 29 ]. Also, LLINs may be temporarily unavailable due to washing or travel.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, all surveys in this study were done in the rainy season so that dry season use could not be observed. But there is good evidence from other sources to suggest that in this dry savannah area with a short and heavy rain period and a long dry period LLIN use is seasonal [25,26]. Therefore, the question arises whether a lower use rate of the cohort nets in the dry season could have contributed to the significantly better physical durability of the monitored LLIN in Zamfara.…”
Section: Discussionmentioning
confidence: 99%